Kader Posyandu Lansia Desa Guwang Tingkatkan Kesehatan Mental Lansia melalui Yoga Bali Marga Rahayu - Putra, I Gede Yudiana; Muryani, Ni Made Sri; Wirawan, I Gusti Bagus (Jurnal SOLMA, 2025)
Background: Older adults are vulnerable to various physical and mental health problems, including degenerative diseases, stress, anxiety, mild depression, loneliness, and cognitive decline. This condition highlights the importance of a holistic approach in elderly health care. The Elderly Posyandu Program in Guwang Village has so far focused mainly on physical health, while mental health has received less attention. Methods: The program was carried out through training for cadres, covering elderly mental health, emotional support strategies, and the practice of Yoga Bali Marga Rahayu as a culturally based relaxation method. Evaluation was conducted using pre-tests, post-tests, and field practice. Results: The pre-test showed that 60% of cadres only understood physical aspects, with an average score of 68%. After the training, the average score increased to 90%, with 90% of cadres able to explain the material and 100% reporting confidence in assisting the elderly. Program implementation showed that 86 elderly participants (91%) attended and enthusiastically engaged in yoga. Mental health education also successfully raised awareness among the elderly to reduce stress, avoid loneliness, and strengthen spirituality. Conclusion: Community health cadre training based on local wisdom effectively improved cadres’ capacity and had a positive impact on the quality of life of the elderly. This approach can serve as a community empowerment model to support elderly mental health holistically.